Development of the FRAND Jurisprudence in China - Jie Gao, Ph.D. (Science and Technology Law Review, 2020)
Standard-essential patents (“SEPs”) are patents that embody industry-adopted technical standards. While standardization presents many benefits, including interoperability of standardized products and lower manufacturing costs, to the consumers and the industries, it may also lead to the “hold-up” problem where a SEP holder demands a high royalty rate from an implementer using the standard-development leverage. To mitigate the hold-up problem, standard-setting organizations often require the participants to agree to license their SEPs to implementers on “fair, reasonable, and non-discriminatory” (“FRAND”) terms. In recent years, disputes concerning FRAND-encumbered patents have arisen frequently around the globe. In particular, China has become an important forum for the worldwide SEP holders and implementers because many telecommunications companies involved in standard setting have significant patent portfolios in China. This Note describes the current status of the FRAND jurisprudence in China. In doing so, this Note analyzes how Chinese courts responded to four key questions—(1) Is the patent owner’s failure to license fairly a breach of contract? (2) Does agreeing to license on FRAND terms waive the right to injunctive relief? (3) How should courts decide whether the proffered license is fair and reasonable? and (4) Is a SEP holder obligated to license its SEP to any willing license seeker?—and compares the answers with those provided by courts in the United States and Europe.